2014
DOI: 10.1093/humrep/deu155
|View full text |Cite
|
Sign up to set email alerts
|

Human in vitro oocyte maturation is not associated with increased imprinting error rates at LIT1, SNRPN, PEG3 and GTL2

Abstract: This study was supported by research funds from Agentschap voor Innovatie door Wetenschap en Technologie (IWT-TBM 110680), Wetenschappelijk Fonds Willy Gepts (WFWG 2011) and German Research Foundation (HA 1374/12-2). There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…However, individual characteristics, such as age or fertility status, and differences in ovarian stimulation from stimulated assisted reproductive technology cycles could still be factors that confound our findings. Nevertheless, our findings of stable CpG methylation during oocyte maturation is reassuringly consistent with an earlier study using unstimulated oocytes and in vitro maturation protocol, which found unchanged CpG methylation of four imprinted genes during in vitro oocyte maturation (Kuhtz et al., 2014). With the rare availability of human oocytes, especially MII oocytes, for research purposes a collective effort from multiple research teams is needed in the future to collect a sample large enough to address all the limitations of sample heterogeneity.…”
Section: Discussionsupporting
confidence: 92%
“…However, individual characteristics, such as age or fertility status, and differences in ovarian stimulation from stimulated assisted reproductive technology cycles could still be factors that confound our findings. Nevertheless, our findings of stable CpG methylation during oocyte maturation is reassuringly consistent with an earlier study using unstimulated oocytes and in vitro maturation protocol, which found unchanged CpG methylation of four imprinted genes during in vitro oocyte maturation (Kuhtz et al., 2014). With the rare availability of human oocytes, especially MII oocytes, for research purposes a collective effort from multiple research teams is needed in the future to collect a sample large enough to address all the limitations of sample heterogeneity.…”
Section: Discussionsupporting
confidence: 92%
“…Using this sensitive technique, we did not find increased rates of imprinting errors in mouse (27), bovine (28), or human IVM oocytes (29). Although these results argue in favor of the notion that imprint establishment is largely correct in human IVM oocytes, concern remains that maintenance of the imprinting after fertilization and throughout further development may be disturbed.…”
mentioning
confidence: 53%
“…Imprinted genes, which acquire their methylation patterns during late oocyte development (1,2), are frequently used as models for studying IVM-induced epigenetic changes in oocytes (24,(27)(28)(29); however, the interpretation of DBS data in somatic tissues is more difficult. Because imprinted genes are differentially methylated, quantification of somatic epimutations requires a single-nucleotide polymorphism to distinguish between the 2 parental alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this, Kuhtz et al performed single-cell methylation analysis using a bisulfite sequencing technique on 71 oocytes from polycystic ovary syndrome patients matured from the germinal vesicle stage to M2 stage as well as 38 in vivo matured control oocytes. 35 There were no significant differences in methylation patterns of maternally or paternally imprinted genes.…”
Section: Oocyte Maturation Manipulation and Epigenetic Eventsmentioning
confidence: 89%